Prognostic significance of electrodiagnostic studies in the Guillain-Barré syndrome. - Raman, P T (1976)
Nerve conduction and needle electromyographic studies were carried out in 50 patients with the Landry-Guillain-Barré syndrome to assess the reliability of this procedure in predicting the prognosis. Two main groups were identified. The first group was characterized by gross abnormalities in nerve conduction and absence of fibrillation potentials during the entire course of the illness. Twenty-five of 31 patients (80.6%) belonging to this group recovered rapidly, and the quality of recovery was good. In 19 patients belonging to the second group, profuse fibrillations were noted within the first four weeks of the illness with or without associated nerve conduction deficits. Recovery in this group was poor (31.5%) and pronounced residual deficits were more common. Electrophysiological studies therefore are of value not only in the diagnosis but also as a reliable prognostic index in this syndrome.